Efeito de diferentes coberturas plásticas na ambiência de estufas agrícolas - Oliveira, Francisco Fábio Chagas de (2023)
Among the factors contributing to the optimal thermal comfort of cultivated plants in a protected environment, translucent coverings play a fundamental role. In this context, this research aimed to investigate the influence of three different types of plastic films (Diffuse, Transparent, and Milky) installed in three agricultural greenhouses in the Fortaleza region, CE, on temperature and relative humidity conditions, with the goal of providing recommendations to optimize greenhouse performance. The experiment was conducted in three agricultural greenhouses located in the experimental area of the Hydraulic and Irrigation Laboratory of the Department of Agricultural Engineering at UFC, Campus do Pici, in Fortaleza, Ceará, Brazil. Each greenhouse was equipped with a different type of plastic film: milky, transparent, and diffuse. To assess the internal environment, 10 monitoring stations were installed, nine inside the greenhouses and one outside. The central stations contained four air relative humidity and temperature sensors (SHT 31 sensor), each installed at heights of 1, 2, 3, and 4 meters. The side stations had three sensors, excluding the sensor at the 4-meter position. The experiment was carried out from March to July 2023, with data collection every 5 minutes, resulting in 12 readings per hour, subsequently treated with linear regression. Analyzing the temperature behavior in the treatments and sub-treatments of the greenhouse with the diffuse film, no statistical difference was observed in temperatures at 4 meters height (T4) with a value of p<0.055. However, humidity at 4 meters showed a significance level of 1%, differing from the other collection stations with a value of 0.006. Temperature and humidity at 2 meters showed a 5% difference. In the case of the transparent film, all collection stations differed at a significance level of 1%, showing greater temperature and humidity variations in the internal environment. The milky film exhibited higher temperature and RH variations in the nine data collection stations. During the 12-hour period, the Diffuse film differed at a 5% level compared to the Transparent film and at a 1% level compared to the Milky film. During the nights, the coverings showed temperature and humidity variations; however, the covering with the diffuse film had the lowest temperatures throughout the experiment and maintained lower variations in air relative humidity.